Performance anxiety: the competitive self and Hollywood's post-crash films of cruelty. Issue 3 (3rd July 2019) - Bayman, Louis
ABSTRACT: This essay identifies a trend present since 2013 in Hollywood, exemplified by Gone Girl (2014), Foxcatcher (2014), Whiplash (2014), Birdman (2014), Nightcrawler (2014), and I, Tonya (2017). Amongst the various things these films have in common, I give special attention to how each features a protagonist engaged in competitive performance, and also in an abusive relationship. This coupling driving each of the films allows us to make a critical reflection upon neoliberalism, which is distinguished by the objective to expand competition into all spheres of life. Lingering on both the cruelty and the performance that competition can involve, these films dramatize certain ways of feeling that register a series of changes from the humanist individualism that informed classical Hollywood. This essay seeks to show how neoliberalism fosters these changes, and how much they alter previously common distinctions between work and intimacy, the notion of an authenticating, indivisible self, and belief in progress and objective reality.